1980
DOI: 10.1590/s0074-02761980000100014
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an enriched plasma membrame subpellicular microtubule fraction of Leishmania mexicana amazonensis

Abstract: A cell fractionation procedure previously developed for Trypanosoma cruzi was applied to isolated the plasma membrane of promastigotes of Leishania mexicana amazonensis. The cell, swollen in an hypotonic mediun, were disrupted in the presence of a nonionic detergent and the membrane fraction isolated by differencial centrifugation. Electron microscopy showed that the fraction consisted of pieces of the plasma membrane associated with subpellicular microtubules. It was also shown that this fraction is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…They found that the subpellicular microtubules remained attached to the plasma membrane, and could be used as a morphological criterion in assessing the purity of the fraction. This association of isolated membranes with microtubules has been confirmed for L. collosoma (Linder & Staehelin 1977), Trypanosoma cruzi (Meyer & De Souza 1976), Trypanosoma brucei (Voorheis et al 1979), Leishmania mexicana (Timm et al 1980), Leishmania donovani (Dwyer 1980), and Trypanosoma lewisi (Dywer & D'Alessandro 1980). In some cases, the microtubules did not remain associated with the plasma membrane (Pereira et al 1978, Franco da Silveira et al 1979, Zingales et al 1979, Rovis & Baekkeskov 1980.…”
Section: Isolation Of the Plasma Membranementioning
confidence: 74%
See 2 more Smart Citations
“…They found that the subpellicular microtubules remained attached to the plasma membrane, and could be used as a morphological criterion in assessing the purity of the fraction. This association of isolated membranes with microtubules has been confirmed for L. collosoma (Linder & Staehelin 1977), Trypanosoma cruzi (Meyer & De Souza 1976), Trypanosoma brucei (Voorheis et al 1979), Leishmania mexicana (Timm et al 1980), Leishmania donovani (Dwyer 1980), and Trypanosoma lewisi (Dywer & D'Alessandro 1980). In some cases, the microtubules did not remain associated with the plasma membrane (Pereira et al 1978, Franco da Silveira et al 1979, Zingales et al 1979, Rovis & Baekkeskov 1980.…”
Section: Isolation Of the Plasma Membranementioning
confidence: 74%
“…The specific activities of Mg 2+ -dependent ATPase and adenyl cyclase in the membrane fraction were two and five times higher, respectively, than in the whole homogenate. Electron-microscopy showed slight contamination with ribosomes (Timm et al 1980).…”
Section: Isolation Of the Plasma Membranementioning
confidence: 98%
See 1 more Smart Citation
“…To obtain a purified plasma membrane fraction from epimastigotes of T. cruzi, cells previously swollen by treatment with Triton X-100 were disrupted using a Dounce-type homogenizer followed by consecutive steps of differential centrifugation and its purity was evaluated by electron microscopy and by testing for enzyme markers. Electron-microscopy showed slight contamination with ribosomes of T. cruzi (Timm et al, 1980). In another approach, cells were ruptured by sonication and the membrane fraction was isolated by differential centrifugation, followed by equilibrium centrifugation on sucrose gradients.…”
Section: Plasma Membranementioning
confidence: 99%
“…Um dos primeiros trabalhos sobre vacinas experimentais de 2ª geração contra as espécies de Leishmania do Novo Mundo data da década de 80(TIMM et al 1980). Nesse trabalho, os autores purificaram frações antigênicas de membrana plasmática de L. (L.) amazonensis e avaliaram sua imunogenicidade em camundongos Swiss.…”
unclassified